Effects of low-frequency noise on cardiac collagen and cardiomyocyte ultrastructure: an immunohistochemical and electron microscopy study - Antunes, Eduardo (2014)
"Introduction: Low-frequency noise (LFN) leads to the development of tissue fibrosis. We previously reported the development of myocardial and perivascular fibrosis and a reduction of cardiac connexin43 in rats, but data is lacking concerning the affected type of collagen as well as the ultrastructural myocardial modifications. Objectives: The aim of this study was to quantify cardiac collagens I and III and to evaluate myocardial ultrastructural changes in Wistar rats exposed to LFN. Methods: Two groups of rats were considered: A LFN-exposed group with 8 rats continuously submitted to LFN during 3 months and a control group with 8 rats. The hearts were sectioned and the mid-ventricular fragment was selected. After immunohistochemical evaluation, quantification of the collagens and muscle were performed using the image J software in the left ventricle, interventricular septum and right ventricle and the collagen I/muscle and collagen III/muscle ratios were calculated. Transmission electron microscopy (TEM) was used to analyze mid-ventricular samples taken from each group. Results: The collagen I/muscle and collagen III/muscle ratios increased in totum respectively 80% (p<0.001) and 57.4% (p<0.05) in LFN-exposed rats. TEM showed interstitial collagen deposits and changes in mitochondria and intercalated discs of the cardiomyocytes in LFN-exposed animals. Conclusions: LFN increases collagen I and III in the extracellular matrix and induces ultrastructural alterations in the cardiomyocytes. These new morphological data open new and promising paths for further experimental and clinical research regarding the cardiac effects of low-frequency noise."